Stem Cell Nanotechnology Methods and Protocols - Turksen, Kursad.; Turksen, Kursad. (Methods in Molecular Biology,, 2013)
Stem Cell Nanotechnology: Methods and Protocols gathers several representative protocols related to the emerging interest in nanotechnology as it relates to stem cell biology. The detailed chapters presented within have been validated for reproducibility and are described in an easy to follow, step-by-step fashion so as to be valuable for not only experts but also novices in the stem cell field.  As with other volumes in the highly successful Methods in Molecular Biology series, chapters conclude with a Notes section, which provides tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Stem Cell Nanotechnology: Methods and Protocols provides both a flavor of the field as it currently is and a source to stimulate new approaches and methodologies by those interested in nanotechnological applications.